2016
DOI: 10.1002/bbb.1709
|View full text |Cite
|
Sign up to set email alerts
|

From lignocellulosic metagenomes to lignocellulolytic genes: trends, challenges and future prospects

Abstract: Lignocellulose is the most abundant biomass on Earth with immense potential to act as a primary resource for the production of a range of compounds currently obtained from fossil fuel sources. However, lignocellulosic feedstocks remain largely underexploited due to the complex mixture of recalcitrant polymers present, whose structural features hinder access to the utilizable monosaccharide reservoir within cellulose. Various fungi and bacteria have been identified that can enzymatically decompose lignocellulos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 132 publications
(154 reference statements)
0
25
0
Order By: Relevance
“…Lignocellulolytic microbial communities, both from aerobic and anaerobic environments, such as those found in soil, compost, rumen, manure, insect guts, mammal guts, and biogas reactors, represent an inter‐taxonomic effort to degrade lignocellulose, and harbor a vast set of genes responsible for biomass utilization. Micro‐organisms are regarded as reservoirs of plant cell wall‐degrading enzymes with great potential in biorefining applications and possible sources of novel strategies and mechanisms for efficient biomass conversion . Multi‐omics approaches, including genomics, transcriptomics, and proteomics, enable the high‐throughput characterization of lignocellulolytic systems, whether isolated species or complex environmental microbial communities, and increase our understanding of the diverse molecular mechanisms underlying lignocellulose breakdown, which is fundamental for the development of enzyme platforms for biorefineries.…”
Section: Omics Approaches For the Screening Of Lignocellulolytic Micrmentioning
confidence: 99%
See 1 more Smart Citation
“…Lignocellulolytic microbial communities, both from aerobic and anaerobic environments, such as those found in soil, compost, rumen, manure, insect guts, mammal guts, and biogas reactors, represent an inter‐taxonomic effort to degrade lignocellulose, and harbor a vast set of genes responsible for biomass utilization. Micro‐organisms are regarded as reservoirs of plant cell wall‐degrading enzymes with great potential in biorefining applications and possible sources of novel strategies and mechanisms for efficient biomass conversion . Multi‐omics approaches, including genomics, transcriptomics, and proteomics, enable the high‐throughput characterization of lignocellulolytic systems, whether isolated species or complex environmental microbial communities, and increase our understanding of the diverse molecular mechanisms underlying lignocellulose breakdown, which is fundamental for the development of enzyme platforms for biorefineries.…”
Section: Omics Approaches For the Screening Of Lignocellulolytic Micrmentioning
confidence: 99%
“…This biochip allows the simultaneous identification and quantification of transcripts of up to 55 220 bacterial GH genes deposited in the CAZy database. Currently, the CAZyChip does not allow detection of fungal genes; however, the authors forecast their inclusion in the platform, given the role of fungal enzymes in biomass degradation and their synergistic action with prokaryotic enzymes . The development of the CAZyChip exemplifies the current trend of valorizing bacteria as key actors in lignocellulose degradation with biorefining potential.…”
Section: Omics Approaches For the Screening Of Lignocellulolytic Micrmentioning
confidence: 99%
“…The knowledge of their enzymatic degradation system could contribute to broaden the sources of biocatalysts with biotechnological impact (Willis et al, 2010; Sun et al, 2013; Scharf, 2015; Batista-García et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are many calls for the search for renewable forms of energy resources. This is as a result of limited areas for petroleum-based fuel production, which are continually reducing [38,39]. Over the years, animal feed and plant built biological materials consisting of carbohydrate have been used as biomass energy resources for alternative fuel production, and the fuels generated from these resources are called biofuels [40,41].…”
Section: Degradation Of Lignocellulose For Biofuel Productionmentioning
confidence: 99%
“…Recently, scientific interest in termite mound soils has increased, because they accommodate vast numbers of bacteria that secrete unusual cellulolytic enzymes that are useful in biofuel industries. For example, Glycosyl hydrolases, a useful enzyme for bioethanol, could be obtained from a termite mound [37,39,49]. As early as 1985, Jaishree and his co-researchers reported that the Cellulomonas species, a cellulose degrading bacteria, was isolated in a termite mound occupied by Odontotermes obesus in a semi-arid region [9].…”
Section: Degradation Of Lignocellulose For Biofuel Productionmentioning
confidence: 99%